2015
DOI: 10.1002/jcb.25287
|View full text |Cite
|
Sign up to set email alerts
|

Lysosomal pH Plays a Key Role in Regulation of mTOR Activity in Osteoclasts

Abstract: Mammalian target of rapamycin (mTOR) is a serine/threonine kinase involved in the regulation of cell growth. It has been shown to play an important role in osteoclast differentiation, particularly at the earlier stages of osteoclastogenesis. mTOR activation and function, as part of mTORC1 complex, is dependent on lysosomal localization and the vacuolar H(+) -ATPase (V-ATPase) activity; however, the precise mechanism is still not well understood. Using primary mouse osteoclasts that are known to have higher lys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
43
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 39 publications
6
43
0
Order By: Relevance
“…Two distinct complexes can be formed by mTOR—mTORC1, which contains raptor as mTOR binding partner and regulates protein synthesis in part through phosphorylation of p70S6K and 4E-BP1, and mTORC2 with rictor as mTOR binding partner, which affects cytoskeletal organization and lipid metabolism (Sarbassov et al, 2005a; Foster and Toschi, 2009; Ma and Blenis, 2009; Laplante and Sabatini, 2013; Gaubitz et al, 2016). Previous studies demonstrated the important role of mTOR in osteoclast differentiation and survival (Glantschnig et al, 2003; Sugatani and Hruska, 2005; Hu et al, 2016; Dai et al, 2017). We have found that mTOR association with raptor and rictor was affected by the nutrient availability during osteoclast differentiation.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Two distinct complexes can be formed by mTOR—mTORC1, which contains raptor as mTOR binding partner and regulates protein synthesis in part through phosphorylation of p70S6K and 4E-BP1, and mTORC2 with rictor as mTOR binding partner, which affects cytoskeletal organization and lipid metabolism (Sarbassov et al, 2005a; Foster and Toschi, 2009; Ma and Blenis, 2009; Laplante and Sabatini, 2013; Gaubitz et al, 2016). Previous studies demonstrated the important role of mTOR in osteoclast differentiation and survival (Glantschnig et al, 2003; Sugatani and Hruska, 2005; Hu et al, 2016; Dai et al, 2017). We have found that mTOR association with raptor and rictor was affected by the nutrient availability during osteoclast differentiation.…”
Section: Discussionmentioning
confidence: 95%
“…mTORC2 (with rictor, mSIN1, proctor, and mLST8) affects cytoskeletal organization and survival (Sarbassov et al, 2005a; Gaubitz et al, 2016). mTOR signaling was shown to be important for osteoclast formation and survival (Glantschnig et al, 2003; Sugatani and Hruska, 2005; Hu et al, 2016; Dai et al, 2017), especially in the setting of experimental bone metastasis (Hussein et al, 2012; Abdelaziz et al, 2014, 2015; Mercatali et al, 2016). Akt has been reported as a target of mTORC2 complex (Sarbassov et al, 2005a), as well as an upstream regulator of mTOR activity as part of the PI3K/Akt pathway (Lee et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…A recent study suggested that mTOR signaling in B cells could indirectly regulate osteoclast formation through regulation of ␤-catenin and RANKL/osteoprotegerin (OPG) (9) and another study showed everolimus can restrain the paracrine pro-osteoclast activity of breast cancer cells (19). mTOR signaling may also play an important role in osteoclast survival and differentiation of osteoclast progenitors (8,20,21). In this study, we found that mTORC1 regulates osteoclast differentiation and formation in a cell-autonomous manner with a conditional knockout mice model.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously demonstrated that mTORC1 activity was significantly upregulated in +/R740S osteoclasts compared to the +/+ cells 17 , suggesting that lysosomal pH also plays a role in mTORC1 regulation. We decided to utilize the unique property of this ‘naturally’ pre-set high lysosomal pH of the R740S osteoclast model to decipher the role of lysosomal pH and the V-ATPases in mTORC1 regulation and lysosomal positioning.…”
Section: Introductionmentioning
confidence: 94%